2005
DOI: 10.1089/jwh.2005.14.61
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Risk of Medication Errors in Women

Abstract: We outline some of the causes of medication errors involving women and recommend ways that healthcare practitioners can prevent some of these errors. Patient safety has become a major concern since the November 1999 release of the Institute of Medicine (IOM) report, "To Err Is Human." Errors involving prescription medications are responsible for up to 7000 American deaths per year, and the financial costs of drug-related morbidity and mortality may be nearly $77 billion a year. The Institute for Safe Medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…Provide written materials at an appropriate reading level. A fifth‐grade reading level is recommended for most practices (Grissinger & Kelly, 2005).…”
Section: Patient Safety Issues In the Primary Care Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Provide written materials at an appropriate reading level. A fifth‐grade reading level is recommended for most practices (Grissinger & Kelly, 2005).…”
Section: Patient Safety Issues In the Primary Care Settingmentioning
confidence: 99%
“…In some reports, Serophene (a drug used to stimulate ovulation) was dispensed instead of Serafem (a selective serotonin reuptake inhibitor prescribed to treat premenstrual dysphoric disorder). Other common women's health medication names involved in medication errors include Femara (used to treat postmenopausal women with cancer progression following antiestrogen therapy) and FemHRT (an estrogen therapy product) (Grissinger & Kelly, 2005). Evidence supports the accuracy of APRN prescribing practices.…”
Section: Prescribing and Medication Errorsmentioning
confidence: 99%
“…As medication errors and correct decision, cognition, and performance of the personnel working in hospital sections are complicated processes, errors can occur in each of the medication processes (5). Occurrence of medication errors can cause serious problems in public health and is considered as a threat to patients' safety (6). These errors are put in one of the 5 categories of medical errors made by the institute of medicine (IOM) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Medication errors occur in most health centers around the world and in 3%-8% of all administrations. (The Joanna Briggs Institute, 2010) Studies have shown that in America, medical errors caused thousands of deaths and close to $77 billion in costs associated with drug events annually (Grissinger & Kelly, 2005).…”
Section: Introductionmentioning
confidence: 99%